Disruptive technology: can the banking industry harness disruption for competitive edge? - LOW, Edgar (Institutional Knowledge at Singapore Management University, 2018)
Disruptive innovation was identified as a phenomenon more than two decades ago by prominent Harvard scholar Clayton Christensen. So you may wonder why established industries are only now waking up to the prospect of digital transformation - the banking industry in particular.